Problem SET 9.1

Download as docx, pdf, or txt
Download as docx, pdf, or txt
You are on page 1of 9

Problem Set 9.1, Page 360.

1-5 komponents and length

1. 𝑃: (1, 1, 0), 𝑄: (6, 2, 0)


𝑣⃗: (𝑣⃗1 , 𝑣⃗2 , 𝑣⃗3 )
𝑣⃗1 = 6 − 1 = 5 𝑣⃗2 = 2 − 1 = 1 𝑣⃗3 = 0 − 0 = 0
𝑣⃗: (5, 1, 0)
|𝑣⃗| = √52 + 12 + 02
|𝑣⃗| = √25 + 1 + 0
|𝑣⃗| = √26
|𝑣⃗| = 5.099019513592785
Sketch |𝑣⃗|
Sketch 𝑣𝑒𝑘𝑡𝑜𝑟 𝒖

2. 𝑃: (1, 1,1), 𝑄: (2, 2, 0)


𝑣⃗: (𝑣⃗1 , 𝑣⃗2 , 𝑣⃗3 )
𝑣⃗1 = 2 − 1 = 1 𝑣⃗2 = 2 − 1 = 1 𝑣⃗3 = 0 − 1 = −1
𝑣⃗: (1, 1, −1)
|𝑣⃗| = √12 + 12 + (−1)2
|𝑣⃗| = √1 + 1 + 1
|𝑣⃗| = √3
|𝑣⃗| = 1.732050807568877
Sketch |𝑣⃗|
Sketch 𝑣𝑒𝑘𝑡𝑜𝑟 𝒖
3. 𝑃: (−3.0, 4, −0.5), 𝑄: (5.5, 0, 1.2)
𝑣⃗: (𝑣⃗1 , 𝑣⃗2 , 𝑣⃗)
𝑣⃗1 = 5.5 − (−3.0) = 8.5 𝑣⃗2 = 0 − 4 = −4 𝑣⃗3 = 1.2 − (−0.5) = 1.7
𝑣⃗: (8.5, −4, 1.7)
|𝑣⃗| = √8.52 + (−4)2 + 1.72
|𝑣⃗| = √72.25 + 16 + 2.89
|𝑣⃗| = √91.14
|𝑣⃗| = 9.546727187890099
Sketch |𝑣⃗|
Sketch 𝑣𝑒𝑘𝑡𝑜𝑟 𝒖

4. 𝑃: (1, 4, 2), 𝑄: (−1, −4, −2)


𝑣⃗: (𝑣⃗1 , 𝑣⃗2 , 𝑣⃗3 )
𝑣⃗1 = (−1) − 1 = −2 𝑣⃗2 = (−4) − 4 = −8 𝑣⃗3 = (−2) − 2 = −4
𝑣⃗: (−2, −8, −4)
|𝑣⃗| = √(−2)2 + (−8)2 + (−4)2
|𝑣⃗| = √4 + 64 + 16
|𝑣⃗| = √84
|𝑣⃗| = 9.16515138991168
Sketch |𝑣⃗|
Sketch 𝑣𝑒𝑘𝑡𝑜𝑟 𝒖
5. 𝑃: (0, 0, 0), 𝑄: (2, 1, −2)
𝑣⃗: (𝑣⃗1 , 𝑣⃗2 , 𝑣⃗3 )
𝑣⃗1 = 2 − 0 = 2 𝑣⃗2 = 1 − 0 = 1 𝑣⃗3 = (−2) − 0 = −2
𝑣⃗: (2, 1, −2)
|𝑣⃗| = √22 + 12 + (−2)2
|𝑣⃗| = √4 + 1 + 4
|𝑣⃗| = √9
|𝑣⃗| = 3
Sketch |𝑣⃗|
Sketch 𝑣𝑒𝑘𝑡𝑜𝑟 𝒖
6-10 find the terminal point Q of the vector v with components as given and initial point P. Find
|𝑣⃗|.

6. 𝑣⃗: (4, 0, 0), 𝑃: (0, 2, 13)


𝑄: (𝑄1 , 𝑄2 , 𝑄3 )
𝑄1 = 4 + 0 = 4 𝑄2 = 0 + 2 = 2 𝑄3 = 13 + 0 = 13
𝑄: (4, 2, 13)
|𝑣⃗| = √42 + 02 + 02
|𝑣⃗| = √16 + 0 + 0
|𝑣⃗| = √16
|𝑣⃗| = 4
1 1 7 3
7. 𝑣⃗: (2 , 3, − 4), 𝑃: (2 , −3, 4)
𝑄: (𝑄1 , 𝑄2 , 𝑄3 )
1 7 8 1 3 2 1
𝑄1 = 2 + 2 = 2 = 4 𝑄2 = 3 + (−3) = 0 𝑄3 = (− 4) + 4 = 4 = 2
1
𝑄: (4, 0, )
2
12 1 2
|𝑣⃗| = √ 2
+ 3 + ( )
2 4

1 1
|𝑣⃗| = √ + 9 +
4 16
|𝑣⃗| = √9.3125
|𝑣⃗| = 3.051638903933426
8. 𝑣⃗: (13.1, 0.8, −2.0), 𝑃: (0,0,0)
𝑄: (𝑄1 , 𝑄2 , 𝑄3 )
𝑄1 = 13.1 + 0 = 13.1 𝑄2 = 0.8 + 0 = 0,8 𝑄3 = (−2.0) + 0 = −2.0
𝑄: (13.1, 0.8, −2.0)
|𝑣⃗| = √13.12 + 0.82 + (−2. 0)2
|𝑣⃗| = √171.61 + 0.64 + 4
|𝑣⃗| = √176.25
|𝑣| = 13.27591804735175
9. 𝑣⃗: (6, 1, −4), 𝑃: (−6, −1, −4)
𝑄: (𝑄1 , 𝑄2 , 𝑄3 )
𝑄1 = 6 + (−6) = 0 𝑄2 = 1 + (−1) = 0 𝑄3 = (−4) + (−4) = −8
𝑄: (0, 0, −8)
|𝑣⃗| = √02 + 02 + (−8)2
|𝑣⃗| = √0 + 0 + 64
|𝑣⃗| = √64
|𝑣⃗| = 8
10. 𝑣⃗: (0, −3, 3), 𝑃: (0, 3, −3)
𝑄: (𝑄1 , 𝑄2 , 𝑄3 )
𝑄1 = 0 + 0 = 0 𝑄2 = (−3) + 3 = 0 𝑄3 = 3 + (−3) = 0
𝑄: (0, 0, 0)
|𝑣⃗| = √02 + 02 + 02
|𝑣⃗| = √0 + 0 + 0
|𝑣⃗| = √0
|𝑣⃗| = 0

11-18 Addition, Scalar Multiplikation

Let 𝑎 = (3, 2, 0) = 3𝑖 + 2𝑗; 𝑏 = (−4, 6, 0) = −4𝑖 + 6𝑗; 𝑐 = (5, −1, 8) = 5𝑖 − 𝑗 + 8𝑘; 𝑑 =


(0, 0, 4) = 4𝑘. Find:
1
11. 2𝑎, 𝑎, −𝑎
2
 2𝑎 = 2(3, 2, 0) = (2𝑥3, 2𝑥2, 2𝑥0) = (6, 4, 0) = 6𝑖 + 4𝑗
1 1 1 1 1 3 3
 𝑎= (3, 2, 0) = ( 𝑥3, 𝑥2, 𝑥0) = ( , 1, 0) = 𝑖 + 𝑗
2 2 2 2 2 2 2
 −𝑎 = −(3, 2, 0) = (−3, −2, 0) = −3𝑖 − 2𝑗
12. (𝑎 + 𝑏) + 𝑐, 𝑎 + (𝑏 + 𝑐)
 (𝑎 + 𝑏) = (3 + (−4), 2 + 6, 0 + 0) = (−1, 8, 0) = −𝑖 + 8𝑗
(𝑎 + 𝑏) + 𝑐 = ((−1) + 5, 8 + (−1), 0 + 8) = (4, 7, 8) = 4𝑖 + 7𝑗 + 8𝑘
 (𝑏 + 𝑐) = (−4 + 5, 6 + (−1), 0 + 8) = (1, 5, 8) = 𝑖 + 5𝑗 + 8𝑘
𝑎 + (𝑏 + 𝑐) = (3 + 1, 2 + 5, 0 + 8) = (4, 7, 8) = 4𝑖 + 7𝑗 + 8𝑘
13. 𝑏 + 𝑐, 𝑐 + 𝑏
 𝑏 + 𝑐 = (−4 + 5, 6 + (−1), 0 + 8) = (1, 5, 8) = 𝑖 + 5𝑗 + 8𝑘
 𝑐 + 𝑏 = (5 + (−4), (−1) + 6, 8 + 0) = (1, 5, 8) = 𝑖 + 5𝑗 + 8𝑘
14. 3𝑐 − 6𝑑, 3(𝑐 − 2𝑑)
 3𝑐 = 3(5, −1, 8) = (3𝑥5, 3𝑥(−1), 3𝑥8) = (15, −3, 24) = 15𝑖 − 3𝑗 + 24𝑘
6𝑑 = 6(0, 0, 4) = (6𝑥0, 6𝑥0, 6𝑥4) = (0, 0, 24) = 24𝑘
3𝑐 − 6𝑑 = (15 − 0, (−3) − 0, 24 − 24) = (15, −3, 0) = 15𝑖 − 3𝑗
 2𝑑 = 2(0, 0, 4) = (2𝑥0, 2𝑥0, 2𝑥4) = (0, 0, 8) = 8𝑘
𝑐 − 2𝑑 = (5 − 0, (−1) − 0, 8 − 8) = (5, −1, 0) = 5𝑖 − 𝑗
3(𝑐 − 2𝑑) = 3(5, −1, 0) = (3𝑥5, 3𝑥(−1), 3𝑥0) = (15, −3, 0) = 15𝑖 − 3𝑗
15. 7(𝑐 − 𝑏), 7𝑐 − 7𝑏
 (𝑐 − 𝑏) = (5 − (−4), (−1) − 6, 8 − 0) = (9, −7, 8) = 9𝑖 − 7𝑗 + 8𝑘
7(𝑐 − 𝑏) = 7(9, −7, 8) = (7𝑥9, 7𝑥(−7), 7𝑥8) = (63, −49, 56)
= 63𝑖 − 49𝑗 + 56𝑘
 7𝑐 = 7(5, −1, 8) = (7𝑥5, 7𝑥(−1), 7𝑥8) = (35, −7, 56) = 35𝑖 − 7𝑗 + 56𝑘
7𝑏 = 7(−4, 6, 0) = (7𝑥(−4), 7𝑥6, 7𝑥0) = (−28, 42, 0) = −28𝑖 + 42𝑗
7𝑐 − 7𝑏 = (35 − (−28), (−7) − 42, 56 − 0) = (63, −49, 56)
= 63𝑖 − 49𝑗 + 56𝑘
9 1 1
16. 2 𝑎 − 3𝑐, 9 (2 𝑎 − 3 𝑐)
9 9 9 9 9 27 27
 𝑎= (3, 2, 0) = ( 𝑥3, 𝑥2, 𝑥0) = ( , 9, 0) = 𝑖 + 9𝑗
2 2 2 2 2 2 2
3𝑐 = 3(5, −1, 8) = (3𝑥5, 3𝑥(−1), 3𝑥8) = (15, −3, 24) = 15𝑖 − 3𝑗 + 24𝑘
9 27 3
𝑎 − 3𝑐 = ( − 15, 9 − (−3), 0 − 24) = (− , 12, −24)
2 2 2
3
= − 𝑖 + 12𝑗 − 24𝑘
2
1 1 1 1 1 3 3
 2 𝑎 = 2 (3, 2, 0) = (2 𝑥3, 2 𝑥2, 2 𝑥0) = (2 , 1, 0) = 2 𝑖 + 𝑗
1 1 1 1 1 5 1 8 5 1 8
𝑐 = (5, −1, 8) = ( 𝑥5, 𝑥(−1), 𝑥8) = ( , − , ) = 𝑖 − 𝑗 + 𝑘
3 3 3 3 3 2 3 3 3 3 3
1 1 3 5 1 8 1 4 8 1 4 8
( 𝑎 − 𝑐) = ( − , 1 − (− ) , 0 − ) = (− , , − ) = − 𝑖 + 𝑗 − 𝑘
2 3 2 3 3 3 6 3 3 6 3 3
1 1 1 4 8 1 4 8
9 ( 𝑎 − 𝑐) = 9 (− , , − ) = (9𝑥 (− ) , 9𝑥 , 9𝑥 (− ))
2 3 6 3 3 6 3 3
3 3
= (− , 12, −24) = − 𝑖 + 12𝑗 − 24𝑘
2 2
17. (7 − 3)𝑎, 7𝑎 − 3𝑎
 (7 − 3)𝑎 = 4𝑎 = 4(3, 2, 0) = (4𝑥3, 4𝑥2, 4𝑥0) = (12, 8, 0) = 12𝑖 + 8𝑗
 7𝑎 = 7(3, 2, 0) = (7𝑥3, 7𝑥2, 7𝑥0) = (21, 14, 0) = 21𝑖 + 14𝑗
3𝑎 = 3(3, 2, 0) = (3𝑥3, 3𝑥2, 3𝑥0) = (9, 6, 0) = 9𝑖 + 6𝑗
7𝑎 − 3𝑎 = (21 − 9, 14 − 6, 0 − 0) = (12, 8, 0) = 12𝑖 + 8𝑗
18. 4𝑎 + 3𝑏, −4𝑎 − 3𝑏
 4𝑎 = 4(3, 2, 0) = (4𝑥3, 4𝑥2, 4𝑥0) = (12, 8, 0) = 12𝑖 + 8𝑗
3𝑏 = 3(−4, 6, 0) = (3𝑥(−4), 3𝑥6, 3𝑥0) = (−12, 18, 0) = −12𝑖 + 18𝑗
4𝑎 + 3𝑏 = (12 + (−12), 8 + 18, 0 + 0) = (0, 26, 0) = 26𝑗
 −4𝑎 = −4(3, 2, 0) = (−4𝑥3, −4𝑥2, −4𝑥0) = (−12, −8, 0) = −12𝑖 − 8𝑗
−4𝑎 − 3𝑏 = (−12 − (−12), −8 − 18, 0 − 0) = (0, −26, 0) = −26𝑗
19. Laws do probs. 12-16 illustrate
Prob. 12, (𝑎 + 𝑏) + 𝑐 = 𝑎 + (𝑏 + 𝑐), (Associativity)
Prob. 13, 𝑏 + 𝑐 = 𝑐 + 𝑏, (Commutativity)
Prob. 14-16, use law 𝑐(𝑎 + 𝑏) = 𝑐𝑎 + 𝑐𝑏
20. Prove Eqs. (4) and (6).
Eqs. (4)
a. 𝑎 + 𝑏 = 𝑏 + 𝑎
𝑎(𝑎1 , 𝑎2 , 𝑎3 ), 𝑏(𝑏1 , 𝑏2 , 𝑏3 )
𝑎 + 𝑏 = ( 𝑎1 + 𝑏1 , 𝑎2 + 𝑏2 , 𝑎3 + 𝑏3 )
𝑏 + 𝑎 = ( 𝑏1 + 𝑎1 , 𝑏2 + 𝑎2 , 𝑏3 + 𝑎3 )
𝑎1 + 𝑏1 = 𝑏1 + 𝑎1 , 𝑎2 + 𝑏2 = 𝑏2 + 𝑎2 , 𝑎3 + 𝑏3 = 𝑏3 + 𝑎3
( 𝑎1 + 𝑏1 , 𝑎2 + 𝑏2 , 𝑎3 + 𝑏3 ) = ( 𝑏1 + 𝑎1 , 𝑏2 + 𝑎2 , 𝑏3 + 𝑎3 )
b. (𝑎 + 𝑏) + 𝑐 = 𝑎 + (𝑏 + 𝑐)
𝑎(𝑎1 , 𝑎2 , 𝑎3 ), 𝑏(𝑏1 , 𝑏2 , 𝑏3 ), 𝑐(𝑐1 , 𝑐2 , 𝑐3 )
 (𝑎 + 𝑏) = ( 𝑎1 + 𝑏1 , 𝑎2 + 𝑏2 , 𝑎3 + 𝑏3 )
(𝑎 + 𝑏) + 𝑐 = ( 𝑎1 + 𝑏1 + 𝑐1 , 𝑎2 + 𝑏2 + 𝑐2 , 𝑎3 + 𝑏3 + 𝑐3 )
 (𝑏 + 𝑐) = ( 𝑏1 + 𝑐1 , 𝑏2 + 𝑐2 , 𝑏3 + 𝑐3 )
𝑎 + (𝑏 + 𝑐) = ( 𝑎1 + 𝑏1 + 𝑐1 , 𝑎2 + 𝑏2 + 𝑐2 , 𝑎3 + 𝑏3 + 𝑐3)
(𝑎 + 𝑏) + 𝑐 = 𝑎 + (𝑏 + 𝑐)
c. 𝑎 + 0 = 0 + 𝑎 = 𝑎
 𝑎 + 0 = ( 𝑎1 + 0, 𝑎2 + 0, 𝑎3 + 0) = 𝑎
 0 + 𝑎 = ( 0 + 𝑎1 , 0 + 𝑎2 , 0 + 𝑎3 ) = 𝑎
𝑎+0= 0+𝑎 = 𝑎
d. 𝑎 + (−𝑎) = 0
𝑎(𝑎1 , 𝑎2 , 𝑎3 ), −𝑎(−𝑎1 , −𝑎2 , −𝑎3 )
𝑎 + (−𝑎) = ( 𝑎1 + (−𝑎1 ), 𝑎2 + (−𝑎2 ), 𝑎3 + (−𝑎3 )) = ( 𝑎1 − 𝑎1 , 𝑎2 − 𝑎2 , 𝑎3 − 𝑎3 )
( 𝑎1 − 𝑎1 , 𝑎2 − 𝑎2 , 𝑎3 − 𝑎3 ) = (0, 0, 0) = 0
Eqs. (6)
a. 𝑐(𝑎 + 𝑏) = 𝑐𝑎 + 𝑐𝑏
𝑎(𝑎1 , 𝑎2 , 𝑎3 ), 𝑏(𝑏1 , 𝑏2 , 𝑏3 )
 𝑐(𝑎 + 𝑏) = ( 𝑐(𝑎1 + 𝑏1 ), 𝑐(𝑎2 + 𝑏2 ), 𝑐(𝑎3 + 𝑏3 ))
𝑐𝑎(𝑐𝑎1 , 𝑐𝑎2 , 𝑐𝑎3 )
𝑐𝑏(𝑐𝑏1 , 𝑐𝑏2 , 𝑐𝑏3 )
 𝑐𝑎 + 𝑐𝑏 = (𝑐𝑎1 + 𝑐𝑏1 , 𝑐𝑎2 + 𝑐𝑏2 , 𝑐𝑎3 + 𝑐𝑏3 )
(𝑐𝑎1 + 𝑐𝑏1 , 𝑐𝑎2 + 𝑐𝑏2 , 𝑐𝑎3 + 𝑐𝑏3 ) = ( 𝑐(𝑎1 + 𝑏1 ), 𝑐(𝑎2 + 𝑏2 ), 𝑐(𝑎3 + 𝑏3 ))
𝑐(𝑎 + 𝑏) = 𝑐𝑎 + 𝑐𝑏
b. (𝑐 + 𝑘)𝑎 = 𝑐𝑎 + 𝑘𝑎
 (𝑐 + 𝑘)𝑎 = ((𝑐 + 𝑘)𝑎1 , (𝑐 + 𝑘)𝑎2 , (𝑐 + 𝑘)𝑎3 )
𝑐𝑎(𝑐𝑎1 , 𝑐𝑎2 , 𝑐𝑎3 )
𝑘𝑎(𝑘𝑎1 , 𝑘𝑎2 , 𝑘𝑎3 )
 𝑐𝑎 + 𝑘𝑎 = (𝑐𝑎1 + 𝑘𝑎1 , 𝑐𝑎2 + 𝑘𝑎2 , 𝑐𝑎3 + 𝑘𝑎3 )
(𝑐𝑎1 + 𝑘𝑎1 , 𝑐𝑎2 + 𝑘𝑎2 , 𝑐𝑎3 + 𝑘𝑎3 ) = ((𝑐 + 𝑘)𝑎1 , (𝑐 + 𝑘)𝑎2 , (𝑐 + 𝑘)𝑎3 )
(𝑐 + 𝑘)𝑎 = 𝑐𝑎 + 𝑘𝑎
c. 𝑐(𝑘𝑎) = (𝑐𝑘)𝑎
𝑘𝑎(𝑘𝑎1 , 𝑘𝑎2 , 𝑘𝑎3 )
 𝑐(𝑘𝑎) = 𝑐𝑘𝑎(𝑐𝑘𝑎1 , 𝑐𝑘𝑎2 , 𝑐𝑘𝑎3 )
 (𝑐𝑘)𝑎 = 𝑐𝑘𝑎(𝑐𝑘𝑎1 , 𝑐𝑘𝑎2 , 𝑐𝑘𝑎3 )
𝑐(𝑘𝑎) = (𝑐𝑘)𝑎
d. 1𝑎 = 𝑎
1𝑎(1𝑥𝑎1 , 1𝑥𝑎2 , 1𝑥𝑎3 ) = 𝑎(𝑎1 , 𝑎2 , 𝑎3 ) = 𝑎

21-25 Forces, Resultant

21. 𝑝 = (2, 3, 0) = 2𝑖 + 3𝑗
𝑞 = (0, 6, 1) = 6𝑗 + 𝑘
𝑢 = (2, 0, −4) = 2𝑖 − 4𝑘
𝑅 = 𝑝 + 𝑞 + 𝑢 = (2𝑖 + 3𝑗) + (6𝑗 + 𝑘) + (2𝑖 − 4𝑘) = (2 + 2)𝑖 + (3 + 6)𝑗 + (1 − 4)𝑘
= 4𝑖 + 9𝑗 − 3𝑘

𝑅 = (4, 9, −3)
22. 𝑝 = (1, −2, 3) = 𝑖 − 2𝑗 + 3𝑘
𝑞 = (3, 21, −16) = 3𝑖 + 21𝑗 − 16𝑘
𝑢 = (−4, −19, 13) = −4𝑖 − 19𝑗 + 13𝑘
𝑅 = 𝑝 + 𝑞 + 𝑢 = (𝑖 − 2𝑗 + 3𝑘) + (3𝑖 + 21𝑗 − 16𝑘) + (−4𝑖 − 19𝑗 + 13𝑘)
= (1 + 3 − 4)𝑖 + (−2 + 21 − 19)𝑗 + (3 − 16 + 13)𝑘 = 0𝑖 + 0𝑗 − 0𝑘
𝑅 = (0, 0, 0)
23. 𝑝 = (8, −1, 0) = 8𝑖 − 𝑗
1 4 1 4
𝑞 = ( , 0, ) = 𝑖 + 𝑘
2 3 2 3
17 11 17 11
𝑢 = (− , 1, ) = − 𝑖 + 𝑗 + 𝑘
2 3 2 3
1 4 17 11
𝑅 = 𝑝 + 𝑞 + 𝑢 = (8𝑖 − 𝑗) + ( 𝑖 + 𝑘) + (− 𝑖 + 𝑗 + 𝑘)
2 3 2 3
1 17 4 11
= (8 + − ) 𝑖 + (−1 + 1)𝑗 + ( + ) 𝑘 = 5𝑘
2 2 3 3
𝑅= (0, 0, 5)
24. 𝑝 = (−1, 2, −3) = −𝑖 + 2𝑗 − 3𝑘
𝑞 = (1, 1, 1) = 𝑖 + 𝑗 + 𝑘
𝑢 = (1, −2, 2) = 𝑖 − 2𝑗 + 2𝑘
𝑅 = 𝑝 + 𝑞 + 𝑢 = (−𝑖 + 2𝑗 − 3𝑘) + (𝑖 + 𝑗 + 𝑘) + (𝑖 − 2𝑗 + 2𝑘)
= (−1 + 1 + 1)𝑖 + (2 + 1 − 2)𝑗 + (−3 + 1 + 2)𝑘 = 𝑖 + 𝑗
𝑅 = (1, 1, 0)
25. 𝑝 = (3, 1, −6) = 3𝑖 + 𝑗 − 6𝑘
𝑞 = (0, 2, 5) = 2𝑗 + 5𝑘
𝑢 = (3, −1, −13) = 3𝑖 − 𝑗 − 13𝑘
𝑅 = 𝑝 + 𝑞 + 𝑢 = (3𝑖 + 𝑗 − 6𝑘) + (2𝑗 + 5𝑘) + (3𝑖 − 𝑗 − 13𝑘)
= (3 + 3)𝑖 + (1 + 2 − 1)𝑗 + (−6 + 5 − 13)𝑘 = 6𝑖 + 2𝑗 − 14𝑘
𝑅 = (6, 2, −14)

You might also like